2019
DOI: 10.1016/j.molp.2019.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of a Retrotransposon for Quenching Genome Instability in Modern Rice

Abstract: Transposable elements (TEs) constitute the most abundant portions of plant genomes and can dramatically shape host genomes during plant evolution. They also play important roles in crop domestication. However, whether TEs themselves are also selected during crop domestication has remained unknown. Here, we identify an active long terminal repeat (LTR) retrotransposon, HUO, as a potential target of selection during rice domestication and breeding. HUO is a low-copy-number LTR retrotransposon, and is active unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…For example, in rice, salt, heat and drought stresses can induce the expression of a long terminal repeat (LTR) retrotransposon, HUO, which is subjected to RdDM-mediated gene silencing. Multiple HUO copies may trigger genomic instability by changing global DNA methylation and small RNA biogenesis, which may result in decreased disease resistance and yield penalty (Peng et al, 2019). SpPKE1, a tomato proline-, lysine-, and glutamic-rich type gene isolated from abiotic-resistant species (Solanum pennellii LA0716), confers salt tolerance in tomato and tobacco.…”
Section: Salt Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in rice, salt, heat and drought stresses can induce the expression of a long terminal repeat (LTR) retrotransposon, HUO, which is subjected to RdDM-mediated gene silencing. Multiple HUO copies may trigger genomic instability by changing global DNA methylation and small RNA biogenesis, which may result in decreased disease resistance and yield penalty (Peng et al, 2019). SpPKE1, a tomato proline-, lysine-, and glutamic-rich type gene isolated from abiotic-resistant species (Solanum pennellii LA0716), confers salt tolerance in tomato and tobacco.…”
Section: Salt Stressmentioning
confidence: 99%
“…Modulation of stress responses (Peng et al, 2019) Oryza sativa Heat, salt, cold stress Increased 6mA levels in heat and salt stress, decreased 6mA levels in cold stress Regulation of plant responses to environmental stresses (Zhang Q. et al, 2018) Oryza sativa Heat stress Decreased DNA methylation levels of OsFIE1…”
Section: Activation Of An Ltr Retrotransposon Huomentioning
confidence: 99%
“…A number of studies demonstrated that LTR-RTs serve as a major driving force for genome size evolution [ 2 , 3 , 11 , 12 , 13 ]. In addition, studies of model and non-model species have shown that LTR-RTs exert tremendous effects on shaping chromosome structure [ 14 ], maintenance of genome stability [ 15 ], formation of specific genome regions [ 16 , 17 ], gene exonization and intronization [ 18 , 19 ], and gene regulation [ 20 , 21 ]. Specifically, several reports showed that LTR-RTs can influence the nearby gene expression and thereby change the phenotype of the species [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The biological significance of this molecular pathway operating under heat stress conditions to restrict retrotransposon activity in developing male germ cells may be to prevent the widespread transmission of unwanted or deleterious mutations in wind-pollinated plants such as grasses [34][35][36] . The manipulation of this molecular mechanism in crops will undoubtedly become a useful strategy in future efforts to enhance male fertility and sustain seed productivity under unpredictable and stressful climate conditions.…”
Section: Introductionmentioning
confidence: 99%